Analisis Pola Frasa dan Kalimat dalam Teks Berita pada Buku Bahasa Indonesia Kelas VII Kurikulum Merdeka - Amanda Ivani; Hanuun Dhiyaa Putri Ari; Kejora Padmarani; Tri Karyanti; Asep Purwo Yudi Utomo; Vera Krisnawati (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
News texts have an important role in life. Each sentence in the news text contains one or more information depending on the type of sentence used. The length of sentences in a news text makes it difficult for readers to digest the information presented. For this reason, this research is more focused on analyzing the phrases and sentences contained in news text excerpts. The goal is to make it easier for readers to understand the information in a sentence. Theoretically, this research is useful for adding insight into several types of phrases and sentences in Indonesian. The practical benefits obtained are in the form of ease in determining the core information of a phrase or sentence in a news text. This research is descriptive qualitative research that uses a pragmatic approach. The theoretical approach used in this research is the syntactic approach. The data used is in the form of news text excerpts from class VII Indonesian books which are suspected of having endocentric and exocentric phrases as well as single sentences and compound sentences. Retrieval of research data using literature study techniques, namely observing and noting. The data was then analyzed using the Miles and Huberman technique combined with the distribution method in sorting the data. The results of this study are presented informally. From the research results of five news texts in class VII Indonesian books, 50 data were found which included 7 coordinating endocentric phrases, 10 attributive endocentric phrases, 4 appositive endocentric phrases, 9 directive exocentric phrases, 2 non-directive exocentric phrases, and 8 single sentences and 10 sentences compound.